2022
DOI: 10.1002/aic.17653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the degree of rate control via automatic differentiation

Abstract: The degree of rate control (DRC) quantitatively identifies the kinetically relevant (sometimes known as rate‐limiting) steps of a complex reaction network. This concept relies on derivatives which are commonly implemented numerically, for example, with finite differences (FDs). Numerical derivatives are tedious to implement, and can be problematic, and unstable or unreliable. In this study, we demonstrate the use of automatic differentiation (AD) in the evaluation of the DRC. AD libraries are increasingly avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Preliminary steps were done by performing a degree of rate control (DRC) analysis, but unfortunately we faced numerical instabilities with the evaluation of numerical derivatives. Finite difference method has already been reported problematic previously, [70] especially in transient kinetics where the magnitude of the finite-size perturbation can affect the convergence of the dynamic steady-state. [71] Besides, it is important to point out that Pt 4 Ge 3 will also get poisoned eventually at higher CO pressures.…”
Section: Microkinetic Simulationsmentioning
confidence: 99%
“…Preliminary steps were done by performing a degree of rate control (DRC) analysis, but unfortunately we faced numerical instabilities with the evaluation of numerical derivatives. Finite difference method has already been reported problematic previously, [70] especially in transient kinetics where the magnitude of the finite-size perturbation can affect the convergence of the dynamic steady-state. [71] Besides, it is important to point out that Pt 4 Ge 3 will also get poisoned eventually at higher CO pressures.…”
Section: Microkinetic Simulationsmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsenergylett.4c00365. List of variables; complete microkinetic model equations and computational methods; brief literature review of kinetic scaling relations and barriers reported for the OER; method for estimating bounds of the reversible activation barrier; additional static catalyst simulation results; additional programmable catalyst simulation results; additional refs (PDF) …”
mentioning
confidence: 99%